Analisis Perlakuan Akuntansi Untuk Aset Bersejarah (Studi Pada Pengelolaan Museum Brawijaya Malang) - Khalid Izzuddin Wafiq; Noor Shodiq Askandar; M. Cholid Mawardi (Universitas Islam Malang, 2023)
This study aims to explain the form of accounting treatment (recognition, measurement, presentation and disclosure) in the financial reporting of historic assets. Researchers set the Brawijaya Ijen Museum as a research location. The research subjects used by researchers were the Head of the Brawijaya Ijen Museum, the Brawijaya Ijen Museum Staff and the Rindam V Brawijaya Staff. The object of research in this study is a form of accounting treatment in which there is recognition, measurement, presentation, and disclosure in the financial reporting of historic assets of the Brawijaya Ijen Museum. While researchers used observation, interviews, internet searching and documentation as data collection techniques. The research method used is qualitative by using data reduction, data presentation and drawing conclusions and verification.The results of this study indicate that the Brawijaya Ijen Museum already has those that are in accordance with the SAP and those that are not yet in accordance with the applicable SAP. All collection objects contained in the Brawijaya Ijen Museum are gifts or gifts. Therefore, all units are recorded at a value of Rp.0. (zero) in the financial statements. According to the existing measurement results, the Brawijaya Ijen Museum has recorded all units in the Financial Report with a value of Rp.0 (zero) and is in accordance with the SAP. In this case, the researcher concludes that the Brawijaya Ijen Malang Museum is included in the Special Museum. It is said to be a special museum because this museum stores all information, documents and relics of the Indonesian Army from the colonial era to Indonesian independence.Keywords: Accounting Treatment and Historic Assets